PENINGKATAN SKILL PENYUSUNAN LAPORAN ARUS KAS BAGI SISWA SEKOLAH MENENGAH KEJURUAN - Challen, Auliffi Ermian; Fitri, Hadiati; Hasan, Nida Nadya (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2022)
The purpose of preparing a cash flow statement is to determine the realization of the company's cash receipts and disbursements so that the potential for cash realization in the future can be known. There are two methods of preparing cash flow statements: direct and indirect. However, due to a lack of understanding of the stages of preparing cash flow reports, there are still SMK students who have not been able to make cash flow reports. The purpose of this training is to increase students' competence in preparing cash flow reports using the direct and indirect methods using Microsoft Excel. The target of this training is students at SMK Negeri 14 Jakarta. Activities are carried out through lectures, discussions, practices, and mentoring. The result is that 70% of participants have been able to compile direct and indirect cash flow reports using the Microsoft Excel application.